Tkachuk, I., Hladchuk, O., Vinnychuk, O. Impact of changes in macroeconomic indicators on banking indicators in Ukraine. Management Theory and Studies for Rural Business and Infrastructure Development. 2022. Vol. 44. No. 4: Pp. 461-481. - Ткачук, Ірина Ярославівна; Гладчук, Ольга Михайлівна; Вінничук, Олена Юріївна (My University, 2022)
The aim of the article is to study the mutual influence of the main performance indicators of the banking system of Ukraine and macroeconomic indicators of Ukraine at the present stage of its operation to outline the main factors that will promote the formation of a methodology for studying the essence of the basic processes in the functioning of banks, identifying obstacles to their development and developing effective mechanisms to improve their further activities. As a result of the study, the authors developed a multifactor model of the influence of factors on the performance of banks and used the method of canonical correlations to find the maximum correlations between groups of variables. There is a close correlation between the performance of banks and macroeconomic indicators of the country. The results of the canonical analysis confirmed that the relationship between the selected performance indicators and the selected determinants should be studied in terms of individual performance indicators of banks to form a system of scenarios for the development of these indicators depending on selected factors using the scenario method. The possibility of achieving positive changes in the banking system of Ukraine by influencing the resulting indicators of each of the significant equations through the management of specific significant factor variables is analyzed. Correlation-regression and scenario analysis makes it possible to state that the state policy should be pursued to manage a given set of factors that have a positive impact on banks' performance, promote bank capital growth, number of legal entities, average monthly salary, stability of the National Bank of Ukraine discount rate, etc.
Keywords: bank, performance indicators of banks, macroeconomic indicators, factors influencing banking activity